Politics and emotions the Obama phenomenon - Engelken-Jorge, Marcos; Ibarra Güell, Pedro; Moreno del Río, Carmelo; SpringerLink (Online Service). (Wiesbaden VS Verlag für Sozialwissenschaften, 2011)
Mainstream liberal narratives have often depicted politics as a matter of power and competing interests, disregarding emotions or conceiving them as threats to a rational and well-ordered society. In the last decades, however, this viewpoint has been increasingly challenged by a number of scholars researching on the complex and multidimensional role of emotions in politics. This edited collection aims at providing a concise but comprehensive introduction to this area of research. The essays contained in this volume focus on a single case, the Obama phenomenon, illustrating empirically how the variable ?emotions? can enrich political analysis. Taken together, the essays reflect the plurality of approaches available to the study of politics and emotions and thus contribute to the cutting-edge debates on this fascinating topic
Emotions & contemporary political theory The Political Mind and Its Other Rethinking the Non-Place of Passions in Modern Political Theory Methodological Issues The Influence of Affective States on the Depth of Information Processing Barack Obama and the Political Science of Hope Perspectives on Politics & Emotions The Obama Phenomenon Suspending Disbelief Obama and the Role of Emotions in Political Communication Persuading the Intractable Charisma and Emotional Engagement within the Dialogue of Politics "I'm Still Standing for Hope and Glory!" Reflections on the Obama Phenomenon and the Politics of Resentment vs the Politics of Cosmopolitanism Desiring Politics Wanting More in the Age of Obama
Includes bibliographical references
Electronic reproduction
Keywords: Obama, Barack -- Influence; Political psychology; Communication in politics